Antimicrobial and cytotoxic activity of Alnus glutinosa (L.) Gaertn., A. incana (L.) Moench, and A. viridis (Chaix) DC. extracts (Journal of Health Sciences, 2016)
Introduction: The objective of the present study was to evaluate the antimicrobial and cytotoxic activities of water extracts of leaves and barks from Alnus glutinosa (L.) Gaertn., A. incana (L.) Moench, and A. viridis (Chaix) DC.Methods: The antimicrobial activities of extracts were tested against gram-negative and gram-positive bacteria as well as yeast strains by the agar diffusion method. The cell viability was determined by the Trypan blue dye exclusion method.Results: The largest diameters of inhibition zone (DIZ) were recorded with Staphylococcus aureus ATCC 6538 and Bacillus subtilis 168M. The highest percentage of cell viability was observed with water bark extracts of A. glutinosa (97.46%).Conclusions: Potential antimicrobial properties of A. glutinosa, A. incana, and A. viridis demonstrated in this study, as well as their low levels of toxicity, make them an interesting subject for further studies.